2004
DOI: 10.1002/path.1536
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase in the control of osteoblastic mineralizing activity and bone integrity

Abstract: It has been shown previously that osteoblast differentiation and maintenance of bone mass are impaired in endothelial nitric oxide synthase gene knockout mice. The present study shows by analysis of messenger RNA expression that the transcription factor Cbfa-1/Runx-2 and the bone matrix protein osteocalcin, which are fundamental to osteoblast differentiation, are significantly reduced in neonatal calvarial osteoblasts from these gene knockout mice. Expression of these genes could be restored to wild-type level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 24 publications
3
38
0
1
Order By: Relevance
“…26 Blocking of either cyclooxygenase-2 (COX-2), the key enzyme for mechanically induced PG production, or NOS could prevent mechanically induced bone formation. [27][28][29][30][31] In addition, it has been shown that the lack of eNOS results in defective bone formation, reduced bone volume, and reduced osteoblast activity, [32][33][34] indicating that eNOS is involved in the regulation of bone mass.…”
Section: Introductionmentioning
confidence: 99%
“…26 Blocking of either cyclooxygenase-2 (COX-2), the key enzyme for mechanically induced PG production, or NOS could prevent mechanically induced bone formation. [27][28][29][30][31] In addition, it has been shown that the lack of eNOS results in defective bone formation, reduced bone volume, and reduced osteoblast activity, [32][33][34] indicating that eNOS is involved in the regulation of bone mass.…”
Section: Introductionmentioning
confidence: 99%
“…It has been accepted that eNOS partipicates in the regulation of bone homeostasis (Wimalawansa 2010). eNOS knockout mouse showed impaired osteogenic differentiation (Afzal et al 2004). Bezafibrate can promote the osteogenic differentiation of MC3T3E1 cells through regulating eNOS (Zhong et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Each value is the mean ± SE of five independent experiments. The asterisk indicates a significant difference between the control and test groups (*P < 0.01) BGP protein levels (mg/ml) * * etal maturation (Aguirre et al, 2001;Armour et al, 2001;Afzal et al, 2004). Recently, a biphasic mode of action of NO has been suggested, with lower doses supporting, and higher doses inhibiting, osteoclast and osteoblast function (Gyurkoa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%